Plantation-Based Apiculture in the Tropics: Beekeeper Perceptions and Institutional Constraints in the Acacia Crassicarpa Honey Landscape of Sumatra, Indonesia - Budi Purwanto, Didik; Adalina, Yelin; Meilin, Araz; Raffiudin, Rika; Sahlan, Muhamad (Indonesian Journal of Multidisciplinary Science, 2026)
Plantation landscapes offer ecological resources for commercial beekeeping, yet the sustainability of Acacia crassicarpa honey production in Sumatra faces institutional and market constraints. This study assesses the development potential of plantation-based beekeeping systems by examining productivity performance, honey quality characteristics, stakeholder perceptions, and institutional arrangements. A mixed-methods approach was employed, combining surveys of 60 beekeepers, in-depth interviews with plantation managers and government stakeholders, and laboratory analysis of honey and pollen samples. Quantitative descriptive analysis and qualitative interpretation were used to evaluate production dynamics and value chain constraints. Results indicate an average productivity of approximately 2 kg colony?¹ month?¹, with farm-gate prices averaging around IDR 24,000 kg?¹ across the study areas. At this price level, acacia honey remains positioned primarily as a bulk commodity, which limits its competitiveness in export markets where quality differentiation and certification are increasingly required. The findings suggest that increasing colony numbers and improving productivity could enable economically viable participation in the global honey supply chain. Alternatively, scaling production may support the development of domestic industrial-based honey utilization. Strengthening technical capacity, certification systems, and institutional coordination is therefore essential to enhance competitiveness and support the sustainable development of Indonesia’s plantation-based beekeeping sector